An Evaluation of the Effects of the Transobturator Tape Procedure on Sexual Satisfaction in Women with Stress Urinary Incontinence Using the Libido Scoring System - Narin, Raziye (Hindawi Publishing Corporation, 2013)
Introduction and Hypothesis. Most women experience automatic urine leakage in their lifetimes. SUI is the most common type in women. Suburethral slings have become a standard surgical procedure for the treatment of stress urinary incontinence when conservative therapy failed. The treatment of stress urinary incontinence by suburethral sling may improve body image by reducing urinary leakage and may improve sexual satisfaction. Methods. A total of 59 sexually active patients were included in the study and underwent a TOT outside-in procedure. The LSS was applied in all patients by self-completion of questionnaires preoperatively and 6 months after the operation. General pleasure with the operation was measured by visual analogue score (VAS). Pre- and postoperative scores were recorded and analyzed using SPSS 11.5. Results. Two parameters of the LSS, orgasm and who starts the sexual activity, increased at a statistically significant rate. Conclusion. Sexual satisfaction and desire have partially improved after the TOT procedure.